Mengukir Kebahagiaan dalam Pola Hidup Sederhana, Mungkinkah? - Jodi Wahyudi; Desiyana (Literaksi: Jurnal Manajemen Pendidikan, 2023)
The purpose of this research is to review books to explore and understand the scientific narrative of the book "SIMPLE LIFE" written by Desi Anwar. This descriptive qualitative research examines the relationship between a collection of personal experiences and childhood memories. This book illustrates the importance of adopting a simple mindset and lifestyle in an increasingly complex and busy world. In this journal, I explore the main concepts described in the book, including understandings of happiness, time management, responsible consumption, and deep social relationships, and discuss the positive influence that a simple lifestyle can have in creating individual well-being and society.